Both symbionts and environmental factors contribute to shape the microbiota in a pest insect, Sogatella furcifera - Yang, Kun; Zhang, Hua-Yue; Wang, Peng; Jin, Gui-Xiu; Chu, Dong (Frontiers in Microbiology, 2024)
Introduction Bacterial symbionts are prevalent in arthropods globally and play a vital role in the fitness and resistance of hosts. While several symbiont infections have been identified in the white-backed planthopper Sogatella furcifera, the impact of environmental factors on the microbiota within S. furcifera remains elusive. Methods In this study, a total of 142 S. furcifera individuals from 18 populations were collected from 14 locations across six countries (China, Thailand, Myanmar, Cambodia, Vietnam, and Laos) analyzed with 2bRAD-M sequencing, to examine the effects of symbionts on the microbiota in the S. furcifera population, as well as the vital effects of environmental factors on the bacterial communities. Results and discussion Based on the results, in S. furcifera, the presence of symbionts Wolbachia and Cardinium negatively influenced the abundance of other bacteria, including Enterobacter, Acinetobacter, and Lysinibacillus, while Wolbachia infection significantly decreased the diversity of the microbial community. Moreover, several environmental factors, including longitude, latitude, temperature, and precipitation, affected the abundance of symbionts and microbiota diversity in S. furcifera. These results collectively highlight the vital role of Wolbachia in S. furcifera microbiota, as well as the intricate effects of environmental factors on the bacterial communities of S. furcifera.